2018
DOI: 10.1038/s41598-018-20884-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of episodic memory decay across the adult life span

Abstract: The ability to remember the details of our own experiences declines gradually as we get old. The reason for this decay has been attributed to several factors besides age, such as education, nutrient intake and health status. However, the influence of these factors has mainly been examined individually and rarely together. Here we identify those factors that jointly act as mediators of episodic memory decay across the adult life span. We examined source memory in a lifespan sample of 1557 healthy adults. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
(35 reference statements)
2
15
1
Order By: Relevance
“…The findings of age-invariance in the probability of successful memory retrieval in the current experiments contrast with previous reports of age-related declines in episodic recollection success (e.g., Cansino et al, 2018;Simons, Dodson, Bell, & Schacter, 2004).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of age-invariance in the probability of successful memory retrieval in the current experiments contrast with previous reports of age-related declines in episodic recollection success (e.g., Cansino et al, 2018;Simons, Dodson, Bell, & Schacter, 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Traditionally, investigations of age-related changes in episodic memory have focused on examining the effects of older age on measures of retrieval success (e.g., Cansino et al, 2018;Craik & McDowd, 1987;Koutstaal, 2003;Mark & Rugg, 1998;Naveh-Benjamin, 2000).…”
mentioning
confidence: 99%
“…The study included 519 healthy adults between the ages of 61 and 80 (265 women and 254 men); their average age was 70.2 ± 5.4 years (mean ± SD), and they had 13.3 ± 4.5 years of formal education. This subsample was drawn from a larger sample based on the participants’ age (Cansino et al, 2018a). Participants were recruited in Mexico City through advertisements, appeals to community groups, flyers, and word of mouth.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning its development from early to late adulthood, several cross-sectional studies conducted in large groups of participants ( N > 100) with wide age ranges found no effect of age on estimation performance ( Bullard et al , 2004 ; Della Sala et al , 2004 ; Scarpina et al , 2015 ). The results of another cross-sectional study suggest that cognitive estimation performance might even improve until old age ( MacPherson et al , 2014 ), in sharp contrast to the decline of many intellectual abilities observed between middle and late adulthood ( Gauvrit et al , 2017 ; Cansino et al , 2018 ).…”
Section: Introductionmentioning
confidence: 96%